The Influence of Job Placement, Career Development, and Organizational Climate on Employee Loyalty Mediated By Job Satisfaction At Serang Raya University - Hairul Nufus; Andari Andari (International Journal of Economics and Management Sciences, 2024)
This research aims to determine the influence of job placement, career development and organizational climate on employee loyalty which is mediated by job satisfaction at Serang Raya University. The form of research used is descriptive and verification research. Descriptive is a form of research aimed at describing existing phenomena, both natural phenomena and man-made phenomena. The population in this study was all educational staff within Serang Raya University, totaling 158 people. Then, in determining the number of samples for the Employee Loyalty variable, the author used the Slovin formula with a standard error of 5%. The research results showed that work placement had a positive and significant influence. on job satisfaction, career development has a positive and significant effect on job satisfaction, organizational climate has a positive and significant effect on job satisfaction, work placement has no significant effect on employee loyalty, career development has a positive and significant effect on employee loyalty, organizational climate has a positive but not significant effect on employee loyalty, job satisfaction has a positive and significant effect on employee loyalty and there is no significant evidence that job satisfaction mediates the relationship between job placement, career development, or organizational climate and employee loyalty. This study is limited to a single institution (Serang Raya University), so the findings may not be generalizable to other organizations. Additionally, there is insufficient evidence that job satisfaction mediates the relationship between job placement, career development, and organizational climate with employee loyalty, necessitating further research with a more comprehensive approach.